The Excellence of Lecturer HR in Increasing Competition In Research-Based Higher Education Services - Fitria Damayanti; Novdin M Sianturi; Antono Damayanto; B.M.A.S. Anaconda Bangkara; Dina Hajja Ristianti (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2023)
This study aims to discuss strategies to improve the quality of the apostles in efforts to increase university competitiveness through research activities. To discuss this theme, we have conducted a series of data searches on several data sources that discuss the issue of increasing lecturer resources and the quality of intensity through research activities. We analyze the collected data under a phenomenological approach, which includes organizing data, coding data, in-depth evaluation, and high interpretation to improve the quality and reliability of study findings. An electronic population data search in several related kinds of literature, then we designed it in a descriptive collection. Based on the findings and discussion, we have concluded that efforts to excel in improving the quality of lecturers through improving the quality of understanding are a strategy that several universities in developed countries have pursued. The same strategy can be applied by Indonesian investment to increase the ranking and design of universities through research activities carried out by lecturers.